The development of Saudi Arabian Entrepreneurship and Knowledge society - Alessa, Adlah A.; Alajmi, Shayma Hussain (International Journal of Management Excellence (ISSN: 2292-1648), 2017)
The current knowledge society has become a major factor in the distinction between countries, as many of them have sought to focus on knowledge and information; considering it the main resource. This study aims to identify the subject of the entrepreneurship's development in Saudi Arabia and contributes to the attainment of the knowledge society. We used the analytical descriptive approach and the questionnaire tool. The study population was represented by the Ministry of Economy and Planning officials in Saudi Arabia. Furthermore, the study’s sample consisted of 80 subjects, among which 60 were valid for analysis. We found that the impact on Saudi Arabia entrepreneurship, project participation and execution are reliant on support and encouragement of the concept itself while the level of education significantly influences the likelihood of project success.